Chemical Contents of Fennel (Foeniculum vulgare var. Dulce) Grown North East Anatolian Region - Dursun, Atilla; Ekinci, Melek (Asian Journal of Chemistry, 2010)
The aim of this study was to assess the chemical content of fennel (Foeniculum vulgare var. dulce) bulb and leaves. The plant species were grown in summer and early autumn and analyzed for their mineral content. When the planting times were compared, there were significant differences in terms of N, P, Zn and Fe contents in leaves and K, Zn, Fe and Mn contents in bulb of fennel vegetable species. The best time to grow fennel was the second planting time in terms of high nutritional value. In general, mineral contents of leaf and bulb were relatively abundant in fennel vegetable species. Therefore, it may provide a source of macro and micro minerals and contribute to taste and colour diets. As a result, fennel vegetable species could be a very important alternative plant species for the region.